DETERMINAN SUSTAINABLE GROWTH PADA PERUSAHAAN SEKTOR BARANG KONSUMEN NON-PRIMER DI INDONESIA - Meiliani, Fuja; Djazuli, Abid; Utami, Dinarossi (MOTIVASI, 2024)
Purpose– This research aims to determine the effect of Profitability (ROA), Activity (TATO), Liquidity (Current Ratio), and Solvency (DER) on Sustainable Growth in the Non-Primary Consumer Goods Sector listed on the Indonesia Stock Exchange. Design/methodology– The population in this study was 151 companies in the non-primary consumer goods sector. The sample used was 102 companies from the 2017-2022 period. The analysis technique used in this research is the quantitative data analysis technique of panel data regression. Based on the regression results with the selected model, namely the Fixed Effect Model, Findings - The results shows that the Profitability Ratio, Activity Ratio, Liquidity Ratio, and Solvency influence sustainable growth in listed Non-Primary Consumer Goods Sector companies on BEI. These financial ratios provide key information about a company's financial health and performance, which in turn influences the company's ability to achieve sustainable growth. Each of these determinants of sustainable growth also reflects the company's stability. The importance of stability is to support sustainable growth as it allows companies to overcome economic challenges and better manage risks.